Using Some Web Based Social Learning Applications for Developing EFL Secondary Stage Students' Writing Skills and Self-Esteem - Helwa, Hasnaa Sabry Abdelhamid Ahmed (جامعة بنها - كلية التربية, 2016)
يهدف البحث الحالي إلى توضيح فاعلية استخدام بعض تطبيقات التعلم الاجتماعي القائم على الأنترنت في تنمية مهارات الكتابة والتقدير الذاتي في اللغة الإنجليزية لدي طلاب المرحلة الثانوية. ويعد هذا البحث من البحوث المختلطة/ المدمجة التي دمجت أساليب البحث الكمية والكيفية معا. وتكونت عينة الدراسة من ثلاثون طالبة تم اختيارهم عشوائيا من طلاب الصف الثاني الثانوي من مدرسة ميت كنانة الثانوية للبنات بمحافظة القليوبية، جمهورية مصر العربية. هذا وقد تم اختيار عينة الدراسة قبل إجراء المعالجة وبعد تطبيق البرنامج القائم على تطبيقات التعلم الاجتماعي القائم على الأنترنت. واشتملت أدوات الدراسة على اختبار في مهارات الكتابة ومقياس في تقدير الذات ومقابلة شبه منظمة. وأشارت نتائج البحث إلى وجود فروق ذات دلالة إحصائية بين درجات الطلاب (عينة الدراسة) في القياس القبلي-البعدي في مهارات الكتابة والتقدير الذاتي في اللغة الإنجليزية لصالح القياس البعدي. وترجع هذه النتائج إلى فاعلية استخدام تطبيقات التعلم الاجتماعي القائم على الأنترنت في تنمية تلك المهارات.
The aim of this research was to investigate the effectiveness of using some web based social learning applications in developing EFL secondary stage students' writing skills and self-esteem. The design of the research was a mixed research methodology. It combined both quantitative and qualitative methods of inquiry. The participants of the study were thirty students enrolled in second year at Met-Kenana Secondary School for Girls. Qalubia Govemorate. Egypt .They tested before and after the intervention. They taught through a program based on some web based social learning applications (Edmodo. Facebook. And Twitter). The instruments of the research included an EFL writing skills test, self-esteem scale, and a semi-structured interview. Results revealed a statistically significant difference between the mean score of the study participants in the pre and post administration of the EFL writing skills and self-esteem in favor of the post administration. These results were ascribed to using some web based social learning applications.
Keywords: التعليم الثانوي -- اللغة الإنجليزية (تعليم) -- تقدير الذاتي -- التعلم الاجتماعى -- مهارات الكتابة